Decentralized model-free loss minimization in distribution grids with the use of inverters - Murzakhanov, Ilgiz; Chatzivasileiadis, Spyros (Sustainable Energy, Grids and Networks, 2023)
Distribution grids are experiencing a massive penetration of fluctuating distributed energy resources (DERs). As a result, the secure and efficient real-time operation of distribution grids becomes a paramount problem. While installing smart sensors and enhancing communication infrastructure improves grid observability, it is computationally impossible for the distribution system operator (DSO) to optimize setpoints of millions of DER units. This paper proposes decentralized model-free algorithms that can actively control converter-connected devices and can operate either stand-alone or in combination with centralized optimization algorithms. We address the problem of loss minimization in distribution grids, and we analytically prove that our proposed algorithms reduce the total grid losses without any prior information about the network, requiring no communication, and based only on local measurements. Our designed local algorithms achieve up to 85% reduction in the power losses by only controlling the injected reactive power compared to the base-case scenario where converters do not provide reactive power support. Going a step further, we combine our proposed local algorithms with a central optimization of a very limited number of converters. The hybrid approaches we propose, achieve the same loss minimization results as a global optimization but with a significantly lower computation and communication burden, and they require central control of up to 5 times fewer resources while offering performance guarantees in case of communication failure. We demonstrate our algorithms in four networks of varying sizes: a 5-bus network, an IEEE 141-bus system, a real Danish distribution system, and a meshed IEEE 30-bus system.